The horizontal gender segregation and its consequences in the masculinised occupation of mechanic (M/F) in the subsector of motor vehicle repair garages in Spain - María del Mar Maira Vidal (Universidade do Porto, 2017)
This paper is based on the results of two research projects of the research group "Women in men's worlds": the research project "Women in men's worlds: Barriers to enter and strategies to overcome them" (Ref.: FEM2011-25228), financed by the National Plan of the Ministry of Economy and Competitiveness between January 2011 and December 2013; and the project "Women in men's worlds: Socialisation, labour organisation, and image" (CSO2014-54339-P), also financed by the National Plan between September 2015 and September 2018. In both research projects we have analysed occupational horizontal gender segregation in masculinised occupations in Spain. In this paper we present the results of both research projects about female garage mechanics, whose training and occupation reveal a very high rate of gender-related segregation or cases of gender-related discrimination and harassment or sexual harassment.